2021
DOI: 10.1093/jrr/rrab121
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of post-radiotherapy survival for bone metastases: a comparison of the 3-variable number of risk factors model with the new Katagiri scoring system

Abstract: We investigated patient survival after palliative radiotherapy for bone metastases while comparing the prognostic accuracies of the 3-variable number of risk factors (NRF) model and the new Katagiri scoring system (Katagiri score). Overall, 485 patients who received radiotherapy for bone metastases were grouped as per the NRF model (groups I, II and III) and Katagiri score (low-, intermediate- and high-risk). Survival was compared using the log-rank or log-rank trend test. Independent prognostic factors were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…It was suggested based on their limited analysis and noted survival among the risk groups that the Combs Prognostic Score should be used in clinical decision making and patient stratification. We observed that in select situations, such as recurrent disease, brain metastases, and spinal cord compression, there is some evidence to guide who may be suitable for retreatment or SBRT based on their life expectancy ( [11,19,22,28,31,32,34,35,38,39,43,44] and [12] (p. 20)). Patients with a longer predicted survival are generally more suitable for longer courses of PRT, as they are more likely to complete their treatment [45].…”
Section: Resultsmentioning
confidence: 93%
“…It was suggested based on their limited analysis and noted survival among the risk groups that the Combs Prognostic Score should be used in clinical decision making and patient stratification. We observed that in select situations, such as recurrent disease, brain metastases, and spinal cord compression, there is some evidence to guide who may be suitable for retreatment or SBRT based on their life expectancy ( [11,19,22,28,31,32,34,35,38,39,43,44] and [12] (p. 20)). Patients with a longer predicted survival are generally more suitable for longer courses of PRT, as they are more likely to complete their treatment [45].…”
Section: Resultsmentioning
confidence: 93%
“…Several solutions have been proposed to overcome these barriers including: the use of tools to improve prognosis prediction [ 18 ], training on PRT for experts in palliative care [ 9 , 10 , 11 ] and on palliative care for ROs [ 13 , 14 , 15 , 16 ], and introduction of pathways and organizational models [ 19 , 20 , 21 , 22 , 23 ], possibly integrated with supportive care programs, specifically dedicated to PRT [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In particular, PRT rapid response programs in which patient assessment and radiotherapy planning and delivery are performed in the shortest time (possibly on the same day) were proposed [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%